Identification of yield coefficients in an E. coli model : an optimal experimental design using genetic algorithms - Veloso, Ana C. A. (2005)
An optimal experimental design for yield coefficients estimation in an unstructured growth model of fed-batch fermentation of E. coli is presented. The feed profile is designed by optimisation of a scalar function based on the Fischer Information Matrix. A genetic algorithm is proposed as the optimisation method due to its efficiency and independence on the initial values.